NANO-SCALE MECHANISMS IN THE FORMATION OF DISPLACIVE TRANSITIONS IN SHAPE MEMORY ALLOYS - Adiguzel, O. (World Scientific Publ Co Pte Ltd, 2013)
Shape memory alloys have a peculiar property to return to a previously defined shape or dimension when they are subjected to variation of temperature. These alloys have the important ability to 'remember' their shape and recover this shape after deformation, and they are used as shape memory elements in devices due to this property. The behavior of these materials is evaluated by the structural changes caused by internal stresses in microscopic scale depending on the external conditions. Shape memory effect is facilitated by martensitic transformation, and shape memory properties are intimately related to the microstructures of the alloy, especially the morphology and orientation relationship between the various martensite variants. Twinning and detwinning processes can be considered as elementary processes activated during the transformation.
International Conference on Physics, Chemistry and Applications of Nanostructures (NANOMEETING) -- MAY 28-31, 2013 -- Minsk, BYELARUS
Keywords: Martensite